Uji Pengaruh Zat Pengatur Tumbuh (ZPT) Air Kelapa Dan Pupuk Organik Cair (POC) Urin Kambing Terhadap Pertumbuhan Setek Bibit Tanaman Lada (Piper Nigrum L) Varietas Malonan 1 - Kusriyanto Kusriyanto; Mahdalena Mahdalena; Hamidah Hamidah (Universitas Widya Gama Mahakam, 2019)
The aim of this study was to determine the best concentration of plant growth regulator (PGR) of coconut water and liquid organic fertilizer (LOF) of goat urine for the growth of cuttings of pepper plants, and to find out the interaction of PGR concentration of coconut water and liquid organic fertilizer of goat urine which is appropriate for the growth of cuttings of pepper plants. The study was conducted for 3 months, from September to November 2017. The study was conducted in Sungai Tempurung Village, Anggana District, Kutai Kertanegara Regency, East Kalimantan Province. The research design used was a 4 x 4 factorial randomized block design with 3 replications. The first factor is the concentration of PGR of coconut water (a) consisting of 4 levels: a0 (control), a1 (150 ml / liter of water), a2 (250 ml / liter of water) and a3 (350 ml / liter of water). The second factor is the concentration of liquid organic fertilizer of goat urine (u) consists of 4 levels: u? ((control), u1 (100 ml / liter of water), u2 (200 ml / liter of water) and u3 (300 ml / liter of water). The concentration treatment of PGR of coconut water showed the results significantly affected the growth of cuttings of pepper plants. a3 treatment produced the highest average growth compared to treatments a0, a1 and a2. The treatment of liquid organic fertilizer of goat urine showed the results significantly affected the growth of cuttings of pepper plants. The u3 treatment produces the highest growth rate compared to treatments u0, u1 and u2. The interaction between concentration treatment of PGR of coconut water and liquid organic fertilizer of goat urine showed the results no significant effect on the growth of cuttings of pepper plants.